Characteristics of Steel Fiber Reinforced Concrete With Recycled Coarse Aggregate - Rahim, Mustaqqim Abdul; Pohan, Omi Yanti; Ab Manaf, Mohd Badrul Hisyam; Ahmad, Ahmad Nur Aizat; Shahidan, Shahiron; Md. Ghazaly, Zuhayr; Bawadi, Nor Faizah; Anudai Anuar, Shamilah; Hassan, Zulkarnain; Ismail, Zul-Atfi; Hong, Teoh Jun (Journal of Civil Engineering, Science and Technology, 2018)
Steel is one of the fibers used in fiber reinforced concrete technology. Steel fibers in concrete help to improve flexural strength and crack resistance. Today, there are critical shortages of natural resources. In this research, waste concrete is being used to produce recycled aggregate. The Recycled Coarse Aggregate (RCA) is partially replaced with the natural coarse aggregate (NCA) in concrete to analyze the mechanical properties of steel fiber reinforced concrete (SFRC). Several tests were conducted, such as compression and flexural tests. Five batches (A, B, C, D and E) of concrete cube and prism samples with different proportions of RCA (0%, 25%, 50%, 75% & 100%) and 1.5% volume fraction of steel fiber were tested, together with one control sample which used 100% NCA and 0% volume fraction of steel fiber. As a result, the control sample achieved 27.32 MPa in compression strength and 0.90 MPa for flexural strength while batch A managed to achieve 48.60 MPa and 1.10 MPa respectively. The cube and prism samples of all batches (A, B, C, D, E) showed decreasing compressive and flexural strength with increasing proportion of RCA in the concrete. Four samples fully achieved more than 20 MPa of compression strength and optimum flexural strength.